IMPACT OF COVID-19 PANDEMIC ON BREAST CANCER SCREENING PROGRAM IN BASRA CITY - Dr. Nawar H. Khalil; Dr. Mustafa S. Shareef (Scholar Express Journals, 2022)
Screening mammography offers the possibility of discovering malignant disease at an early stage, which is consequently treated early, thereby reducing the mortality rate; At the end of 2019, Wuhan city in China, became the centre of an outbreak of pneumonia of unknown cause, , known as severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) ,The World Health Organization (WHO) stated it as a global pandemic on March 11, 2020,in addition to the physical health effects of the virus in infected persons, the pandemic is also causing harmful social and mental health effects. Objective: The purpose of the study is to estimate the attendance rate of women to Early Detecting Clinics of Breast diseases in Basra City. Patients and Methods: across _sectional study was conducted from Feb.2020 to Jan.2021 .A total of 384 females where interviewed to assess the effect of COVID_19 on their attendance to Early Detecting Clinics of Breast diseases in Basra City .data analysed using spss version 26 software.
Keywords: Mammography; Screening; Pandemic; Vaccine